If a tree falls in an empty forest : Problematization of liveness in mixed-music performance. Issue 1 (22nd May 2012) - McLaughlin, Scott
Mixed-music is an interesting site for testing concepts and limitations of direct causality in liveness. The nature of liveness in mixed-music is examined here with respect to practical issues of acoustic blending, and practical issues of what is live in mixed-music. The aesthetics of experimental music are explored as valorizing a different model of performance authenticity that is less reliant on direct instrumental causality. Three case studies are presented of my own works that deliberately undermine the causality model of liveness.